UJI SIFAT FISIKA-KIMIA DAN IDENTIFIKASI FENIL ETIL ALKOHOL MINYAK ATSIRI BUNGA MAWAR HASIL EKSTRAKSI PELARUT - Nur Malasari; RTM Sutamihardja; Amry Syawaalz (Universitas Nusa Bangsa, 2017)
Test of Physical and chemical PropertiesÂ and Identification of Phenyl Ethyl Alcohol of Essential Oil Roses from Solvent ExtractionThe technology of extraction of roses oil currently is developed in small scale industries through distillation. However, this technology has many disadvantages. To overcome these obstacles, it is necessary to do research by using solvent extraction vapor (solvent extraction).This study was conducted to determine the type of solvent and the right ratio of solvent to obtain the highest